Local Labor Markets and the Persistence of Population Shocks - Sebastian Till Braun; Anica Kramer; Michael Kvasnicka (Institute of Labor Economics (IZA), 2017)
This paper studies the persistence of a large, unexpected, and regionally very unevenly distributed population shock, the inflow of eight million ethnic Germans from Eastern Europe to West Germany after World War II. Using detailed census data from 1939 to 1970, we show that the shock had a persistent effect on the distribution of population within local labor markets, but only a temporary effect on the distribution between labor markets. These results suggest that locational fundamentals determine population patterns across but not within local labor markets, and they can help to explain why previous studies on the persistence of population shocks reached such different conclusions.
Keywords: J61; R12; R23; N34; 330; population shock; locational fundamentals; agglomeration economies; regional migration; postwar Germany